Direct Anastomosis of the Donor Hepatic Artery to the Supraceliac Aorta without Extension Graft during Adult Liver Transplant in the Era of Extended Criteria Donors: Report of a Case - Jeffrey Campsen; Paul Russ; Igal Kam (Case Reports in Medicine)
Arguably, one of the most challenging aspects of liver transplant surgery is the hepatic artery reconstruction. When the donor and recipient arteries are normal, this anastomosis can still be difficult. However, when the recipient artery has been dissected or is small other alternative reconstructions must be considered. Routinely, the donor surgery includes removing the iliac artery and vein specifically to aid in alternative reconstruction techniques. With the increase use of extended criteria donors (i.e., specifically age >55) the iliac vessel may be unusable because of atherosclerotic disease. This paper describes revisiting an alternative technique for hepatic artery reconstruction during cadaveric liver transplant when the recipient artery has been dissected and the iliac vessels were unusable secondary to arterial plaque from a 75 yo donor. Herein, we describe the successful anastomosis of the celiac artery with aortic patch from the donor directly to the supraceliac aorta of the adult recipient.